Not just for males: females use song against male and female rivals in a temperate zone songbird. (March 2016) - Krieg, Cara A.; Getty, Thomas
Abstract : Birdsong in temperate zone passerines is a trait under sexual selection in males. Female song is still thought to be rare in this group. Here we show that female song is common in a temperate zone population of house wrens, Troglodytes aedon, and we provide evidence for its functional role in defending against male and female conspecifics. We observed that females sang most frequently at the onset of egg laying, with song becoming less common as incubation approached. Thus, females sang most during the time when eggs were left unguarded and susceptible to conspecific attack. We also conducted playback experiments to test whether conspecific stimuli would induce female song in focal individuals. Playback from both male and female conspecifics elicited strong song responses from resident females, who often vocalized independently from their partners. However, females were more physically aggressive towards female songs than male songs. Finally, females that sang more during these simulated conspecific intrusions ultimately lost fewer eggs to house wren ovicide. These results suggest that female house wren song may have evolved, at least in part, for use in intra- and intersexual competition. These results also highlight how investigating these traditionally male behaviours in female animals can lead to key insights regarding the evolution of sexual dimorphism. Highlights: We measured singing by female house wrens during nest visits and during a playback experiment. Song was common at the start of egg laying when conspecifics threaten reproduction. Females sang most and initiated most vocalizing bouts during conspecific playback. Females were most physically aggressive towards playback of female conspecific songs. Females that sang more to simulated conspecifics lost fewer eggs to wren ovicide.